Evaluation of hydration status following soccer matches of different categories - Daniel Barbosa Coelho; Emerson Rodrigues Pereira; Elisa Couto Gomes; Leonardo Coelho; Danusa Dias Soares; Emerson Silami Garcia (Universidade Federal de Santa Catarina, 2012)
The purpose of this study was to evaluate the hydration status and thermoregulatory responses, during official soccer matches, of soccer players in different categories. The participants of the under-15 (U-15, n=36) and of the under-17 category (U-17, n=14) were placed into different groups according to the amount of time spent in the field: Main group; Partial group; Intermediate group; Control group. The thermoregulatory responses and hydration status were measured. The Main group and the Partial group presented significantly higher water intake, weight loss and sweat rate compared with the Intermediate and Control group (p<0.05). The under-17 players of the Main group had a larger weight difference pre and post match compared with the under-15 players of the same group (p<0.05). It was concluded that an official soccer match altered significantly the hydration status of the players, and it was related with the time spent in the match.